Colombia: un asunto de seguridad regional - Tokatlian, Juan Gabriel (Sociedad y Economía, 2001)
The prevailing Colombian crisis in only the ‘tip of the iceberg’ with respect to the overall situation in the Andean region. In Colombia there are there outstanding features, the partial or complete collapse of the state in large areas of the country, the continuing presence of the lucrative drug trade, and the slow transformation of the armed conflict from one of fragmented guerilla warfare into a open warfare extending throughout the country. The conflict is increasingly affecting urban areas and has all the potential to become a civil war. This scenario has induced United States intervention through the Plan Colombia. Europe remains at a distance and neighboring countries are silent. The situation requires a Latin American initiative similar to that of the Contadora Agreement in the decade of the Eighties when various Central American nations were in civil war. Such an initiative should take into account the prevailing geopolitical realities and involve international civil society.